Návrh metodiky hodnocení důležitosti faktorů angažovanosti pro pracovníky v českých organizacích - Horváthová, Petra; Čopíková, Andrea (Univerzita Pardubice, 2017)
Although the engagement concept has been used in management at least in the past 20 years, the interest of managers, HR specialists and employees about this issue is rising. Many studies proved that only satisfaction and stability, loyalty and devotion do not ensure corresponding relationship between the employees’ performance and business results and therefore it is desirable to concentrate on utilizing various measures that support increasing the level of employees’ engagement that can lead to the increase of employees’ performance and by this increasing the performance of organization. Aim of this paper is to propose methodology for evaluating employees’ engagement level and also introduce possible tools of its improvement in organizations operating in the Czech environment. The method used to fulfill the aim was the modification and addition of already existing engagement model, which, however, does not reflect the specifics of Czech environment and differences of young employees on the labor market. The output of this paper include proposal of new engagement model and framework procedure of engagement research, especially questionnaire that can be used to find out importance of engagement factors for employees in Czech organizations.
Proposal of methodology for evaluating the engagement factors importance for employees in Czech organizations
Keywords: engagement; performance; management; employees; M12